Isolated solar angioedema: A systematic review of the literature. Issue 5 (27th March 2021) - Aronovich, Anna; Snast, Igor; Lapidoth, Moshe; Leshem, Yael A.; Enk, Claes D.; Tal, Yuval; Mimouni, Daniel; Hodak, Emmilia; Levi, Assi
Abstract: Solar urticaria is a well‐recognized photodermatosis, sometimes accompanied by angioedema. However, isolated solar angioedema (ISA) is a rare and unrecognized entity. The purpose of our work was to systematically review the available data on ISA. Therefore, a systematic review of studies evaluating ISA was performed. Additionally, a case of a 21‐years‐old patient from our photodermatosis service is presented. The search yielded 421 publications, with 3 eligible for review. Together with our case, 5 cases were included overall. All patients were female. Four out of 5 patients first experienced ISA at childhood or early adulthood (age range 6‐22 years). UVA photoprovocation was positive in the 3 out of the 4 patients who were tested. Improvement was noted following NB‐UVB hardening (2 out of 5 patients) or a short course of oral prednisone (3 out of 5 patients) combined with regular sunscreen application. To conclude, ISA is an extremely rare entity, although it may be underdiagnosed due to lack of awareness. The clinician must consider ISA in the differential diagnosis of angioedema since it can have a detrimental effect on quality of life. Besides sun avoidance, there is no consensus regarding treatment.